STABILITY INDICATING METHOD DEVELOPMENT AND VALIDATION OF METFORMIN AND ERTUGLIFLOZIN BY HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY WITH PDA DETECTION AND ITS APPLICATION TO TABLET DOSAGE FORM - JAGADEESH, KADALI; N, ANNAPURNA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: A sensitive, rapid, accurate, and precise stability indicating high-performance liquid chromatography method was developed and validated for the simultaneous estimation of metformin (MET) and ertugliflozin (ERT). Methods: The planned chromatographic method was developed using Kromasil C18 column using 0.1 M sodium dihydrogen phosphate methanol (50:50, by volume, pH 4.0) as mobile phase system followed by peak area response measurement at 238 nm. The developed method was validated by means of ICH guidelines about system suitability, linearity, sensitivity, selectivity, accuracy, precision, robustness, and specificity. Results: Calibration curves of MET and ERT are linear from 250 to 750 μg/ml and 3.75 to 11.25 μg/ml, respectively. Relative standard deviation is <2.0% and recovery is ̴ 100%. Successfully, the developed method was applied for the simultaneous determination of MET and ERT in tablets and to study degradation of MET and ERT in acidic, alkaline, oxidation, thermal, and photolytic degradation conditions. No obstructions from additional common excipients of tablets and degradants were observed. Conclusion: The results recommended method suitability for the analysis of MET and ERT in quality control laboratories.